2004
DOI: 10.1081/jas-200038447
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Soy Genistein is Associated with Lung Function in Patients with Asthma

Abstract: To determine if micronutrient intake is associated with asthma severity, we administered the Block food frequency questionnaire to participants in a randomized clinical trial of the safety of influenza vaccine for asthmatics. The nutrition substudy included 1033 participants, aged 12-75. Intake of antioxidant vitamins, soy isoflavones, total fruits and vegetables, fats, and fiber was compared with asthma severity at baseline [forced expiratory volume in 1 second (FEV1), peak expiratory flow rate (PEF), asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 46 publications
3
41
0
2
Order By: Relevance
“…The results of the cross-sectional study show that a high dietary intake of soy proteins, including genistein and daidzein, is associated with the reduced prevalence of allergic rhinitis in human, although no significant dose-response relationships were observed (60). Other study based on questionnaire of participants in a randomized clinical trial with patients with asthma revealed that increasing consumption of genistein is associated with better lung function (93).…”
Section: Soy Products -A Source Of Phytoestrogensmentioning
confidence: 93%
“…The results of the cross-sectional study show that a high dietary intake of soy proteins, including genistein and daidzein, is associated with the reduced prevalence of allergic rhinitis in human, although no significant dose-response relationships were observed (60). Other study based on questionnaire of participants in a randomized clinical trial with patients with asthma revealed that increasing consumption of genistein is associated with better lung function (93).…”
Section: Soy Products -A Source Of Phytoestrogensmentioning
confidence: 93%
“…Kalhan et al [127] showed that the asthmatic patients receiving a soy isoflavone supplement for four weeks exhibited a reduction in exhaled NO and ex vivo production of leukotrienes by eosinophils obtained from the blood of these patients. In addition, Smith [128] demonstrated that this flavonoid is associated with improved lung function in more than 1,000 patients studied. Most studies suggest that the mechanism of action of flavonoids is through the inhibition of NF-kB.…”
Section: Clinical Perspectives Of Flavonoid Application In Lung Diseasementioning
confidence: 99%
“…As noted by the authors, relatively little attention has been paid to soy intake in relation to respiratory or allergic diseases. [8][9][10][11] In a cross-sectional study of young adults in Australia, the consumption of soy beverage was associated with an increased prevalence of current asthma, doctor-diagnosed asthma and bronchial hyperresponsiveness. 8 In another cross-sectional study among Japanese pregnant women, dietary intakes of total soy product, soy protein, daidzein, and genistein in the fourth quartile (as compared to the first quartile), were independently associated with a reduced prevalence of allergic rhinitis, although no significant dose-response relations were observed.…”
mentioning
confidence: 99%
“…10 Among asthmatic adults enrolled in a vaccination trial, the authors noted a cross-sectional association between high consumption of genistein and better lung function. 11 Overall, three studies out of four were cross-sectional, and the only longitudinal study was on cough plus phlegm (not asthma). The only study focusing on asthma 8 reported increased risk.…”
mentioning
confidence: 99%